Surgical treatment of cervical subaxial intraspinal extradural cysts using a full-endoscopic uniportal posterior approach. (23rd May 2018) - Ruetten, Sebastian; Hahn, Patrick; Oezdemir, Semih; Baraliakos, Xenophon; Godolias, Georgios; Komp, Martin
Purpose: Symptomatic intraspinal extradural cysts of the cervical subaxial spine are rare, but usually require surgery. Conventional posterior decompression is the gold standard. However, there is increasing experience with endoscopic surgical techniques. The purpose of the study is to evaluate the technical implementation and outcomes of a full-endoscopic uniportal technique via the posterior approach in patients with symptomatic intraspinal extradural cysts of the cervical subaxial spine. Methods: Seven consecutive patients with a subaxial location of symptomatic intraspinal extradural cysts were decompressed in a full-endoscopic uniportal technique via the posterior approach between 2009 and 2015. Imaging and clinical data were collected in follow-up examinations for 18 months. Results: In all cases, the cyst was completely removed and adequate decompression was achieved using the full-endoscopic uniportal technique. One patient developed a dural leak that was sutured and covered intraoperatively. No other complications requiring treatment were observed. All patients had a good clinical outcome with stable regression of the radicular and central nerve pain or neurological deficits. The imaging follow-up showed sufficient decompression in all cases. No evidence was found of increasing instability during the follow-up period. Conclusion: The full-endoscopic uniportal operation with a posterior approach allows the resection of the cyst and can minimize trauma and destabilization and has technical benefits and a low complication rate. It is an alternative surgical method that can offer advantages and is considered by the authors to be the surgical technique of choice for cervical subaxial intraspinal extradural cysts.